2022
DOI: 10.52158/jace.v2i1.343
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Herbarium and Identification of Plants Based on School Environments in MTs. Negeri 2 Gorontalo Regency

Abstract: The introduction of herbariums in schools as a medium to concrete material and support science learning and plant identification based on a school environment that makes it easier to teach material on the structure and function of plants in class VIII at Madrasah Tsanawiyah Negeri 2 Gorontalo district is the goal in this service activity. The stages of activities using an active participatory approach consist of 4 stages, namely 1) preparation; 2) coordination; 3) implementation; 4) evaluation. The number of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Thus, it can be used as learning media. Many research concluded that when students were using herbarium as learning media, it will be more effective than those who did not use it (Dikrullah et al, 2018;Dahlia & Janiarli, 2021;Mamu et al, 2022). Even more, now the development of the herbarium is not only in the form of physical but in the form of digital media (Setiawan et al, 2020;Widodo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it can be used as learning media. Many research concluded that when students were using herbarium as learning media, it will be more effective than those who did not use it (Dikrullah et al, 2018;Dahlia & Janiarli, 2021;Mamu et al, 2022). Even more, now the development of the herbarium is not only in the form of physical but in the form of digital media (Setiawan et al, 2020;Widodo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%